Proteomics: an efficient tool to analyze nematode proteins (The Journal of Plant Protection Sciences, 2022)
Soybean cyst nematode (Heterodera glycines, mixtures that are part of biological research on  SCN) is the most destructive pathogen of varied fronts, from evolutionary investigations  soybean (Glycine max (L.) Merr.), and is to cancer research. Recent advances in mass  responsible for estimated annual yield losses of spectrometry, the establishment of various  $457 to $819 million (2003-2005) in the United protein databases, and availability of high
Keywords: bioinformatic; resulting; molecular